El bioderecho en el siglo XXI (2020)
The rapid pace in the progression of life sciences pushes law in one of its most significant intrinsic features: the principle of certainty. While uncertainty and the modifiability of its results are of normal currency in life sciences, they are especially problematic in law, jeopardizing the very essence of equality and non discrimination. lt is also worth mentioning that life sciences work on a very diverse set of materials and cases that usually differ from each other. Any even minimum specific traits ofbio-objects must be considered so as to avoid an undifferentiated and therefore unreasonable legal regulation. Law as a codified set of general principles also suffers from this perspective. Taking the above into consideration, this article proposes a number of coordinates, which can give biolaw the necessary features to cope with a diflicult, ever-changing and very specific dimension of human knowledge - building, in this way, an open, updated and attentive biolaw for 21st Century life sciences.